COMPARISON OF AUTOLOGOUS BLOOD AND FIBRIN GLUE IN PTERYGIUM EXCISION WITH CONJUNCTIVAL AUTOGRAFT SURGERY: A RANDOMIZED TRIAL. - Singh, Niharika; Singh, Arjun Kumar (Student's Journal of Health Research Africa, 2024)
Background Because it can affect vision, pterygium is a common ocular surface condition that frequently requires surgical intervention. Conventional surgical methods, such as suture-based conjunctival autograft (CAG), are associated with discomfort after surgery and have a high recurrence risk. To examine the safety and effectiveness of fibrin glue vs autologous blood for pterygium excision during CAG surgery, this study was conducted. Methods There were 150 patients in the study, and they were assigned randomly to one of two groups: group 1: autologous blood (75 eyes), or group 2: fibrin glue (75 eyes). Preoperative evaluations of the patients included slit-lamp biomicroscopy and documentation of their visual acuity. The recurrence rate at a 1-year follow-up was the main result. Improvement in visual acuity, intraoperative and postoperative complications, and graft stability were among the secondary outcomes. Chi-square and t-tests were used to analyze the data, with a significance threshold of p<0.05. Results The recurrence rate at 1-year follow-up was significantly lower in the group 2 (6.7%) compared to the group 1 (16%) (p=0.02). Graft stability was better in group 2, with 96% of grafts intact on postoperative day 1, compared to 86.7% in group 1 (p=0.04). The prevalence of complications was similar between the groups, with no significant differences. Both groups showed significant improvements in visual acuity postoperatively (p<0.01), with no difference between the groups. Conclusion For CAG fixation in pterygium surgery, fibrin glue works better than autologous blood, providing improved graft stability and a decreased recurrence rate. Both techniques are equally safe and efficient at raising visual acuity. Recommendations Fibrin glue should be considered the preferred method for CAG fixation in pterygium surgery due to its superior outcomes in terms of recurrence and graft stability. Further studies could explore long-term outcomes and cost-effectiveness.